Knowledge and preventive practice regarding Cardiovascular disease risk factors among undergraduate students at a higher education institution in Kajang, Selangor - Ang, Carolyn Wei San (2025)
Background and Objectives: With the rising burden of premature cardiovascular disease (CVD) mortality among the younger population in Malaysia, understanding awareness and management of CVD risk factors is vital for developing effective, targeted intervention strategies to mitigate early atherosclerotic changes. This study was conducted to study the knowledge and preventive practice regarding cardiovascular disease risk factors among undergraduate students at a higher education institution in Kajang, Selangor.